Making Digital Technology Return to The Essence of Government Affairs: Generative Logic and Resolution Strategy of Digital Administrative Burden - Liu, Yuhan (Transactions on Social Science, Education and Humanities Research, 2024)
Along with the continuous advancement of the digital government construction in our country, in order to effectively build a service-oriented government that the people are truly satisfied with, this article discusses the administrative burden that the digital government brings to the citizens in the implementation process, analyzes the reasons and proposes the solution path, and provides the reference for future research.Based on the interview method, the experience and feelings of different groups in the process of interacting with the digital government are intuitively obtained. The research finds that the learning cost, obedience cost and psychological cost borne by different groups are slightly different, which is related to the service attitude of government staff and the friendliness of product development and design. Relevant departments should improve the working system to improve the quality of the team. Improve the response mechanism and the product temperature; Strengthen digital empowerment, optimize government services and other measures to reduce the administrative burden of citizens in the implementation of digital government.